The Effect of Video-Based Febrile Seizure Management Education on Knowledge of Families with Toddlers in Indonesia - Nopita Pertiwi Putri; T. Abdur Rasyid; Lita Lita (HealthCare Nursing Journal, 2023)
Febrile seizures pose a significant health concern in toddlers, and there is a need to improve family knowledge regarding the appropriate management of these seizures at home. This study aimed to investigate the influence of video-based education on family knowledge of febrile seizure management in toddlers. A quantitative pre-experimental design using a pre-test and post-test approach was employed. The study population consisted of families with toddlers who had a history of febrile seizures, and a consecutive sampling technique yielded a sample size of 15 participants. Data were collected using a modified Guttman scale questionnaire on febrile seizure management, which underwent content validity assessment. Univariate analysis was conducted to examine the central tendency of age, while gender, occupation, and education were presented as frequency distributions. Paired sample T-tests were used for bivariate analysis. The findings indicated that the average age of the respondents was 31.20 years, with 14 participants being female (93.3%). The majority of participants were unemployed (86.7%) and had completed high school education (80.0%). The pre-test knowledge score on febrile seizure management in toddlers was 8.67, which significantly increased to 14.73 in the post-test, with a P-value of 0.000 (<0.05). These results demonstrate the significant influence of video-based education on enhancing family knowledge of febrile seizure management in toddlers. This study suggests that healthcare professionals in primary health center should implement video-based educational programs to educate families about febrile seizure management in toddlers.